What Happens When Science Fiction Is Introduced into Science Classes? - Wang, Mingbin (Science Insights Education Frontiers, 2025)
Science fiction (sci-fi), whether in literature or films and comics, can always spark colorful visions in the audiences. Despite being a genre of speculative fiction, sci-fi works typically includes serious scientific elements. What impacts can they pose on science education if they are introduced in the classroom? Do they have the potential to become significant resources for science education, or will they probably be a source of distraction and causes of misconception in science classes? Extensive research has been conducted for addressing questions like these.